1992
DOI: 10.1084/jem.175.2.583
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of three D/L-like class I molecules from H-2v: indications of an ancestral family of D/L genes.

Abstract: SummaryThe observation that D region alleles cluster into subgroups suggests that the alleles are not all related to each other by linear descent through a single locus. We propose that current alleles are derived from more than one ancestral locus in a manner similar to the origin of the 3~2a immunoglobulin constant region alleles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…An intermediate level of B27 expression was observed in the H-2v haplotype (Nickerson et al 1990) which has a D region organization distinct from the five-gene organization observed in the D d region, and from the H-2 b prototype with only one H-2D gene (Cai and Pease 1992;Stephen et al 1986;Weiss et al 1984;Duran et al 1989). The pattern of expression of the three nonclassical class I genes (D2-D3-D4) mapping between H-2D and H-2L is not known, but it has been reported that some of them can be transcribed and expressed, although with low stability (Cai and Pease 1992;Hedley et al 1990). Thus, transcribed pseudogenes could be using [32m, further limiting the amount of ~32m available.…”
Section: Discussionmentioning
confidence: 99%
“…An intermediate level of B27 expression was observed in the H-2v haplotype (Nickerson et al 1990) which has a D region organization distinct from the five-gene organization observed in the D d region, and from the H-2 b prototype with only one H-2D gene (Cai and Pease 1992;Stephen et al 1986;Weiss et al 1984;Duran et al 1989). The pattern of expression of the three nonclassical class I genes (D2-D3-D4) mapping between H-2D and H-2L is not known, but it has been reported that some of them can be transcribed and expressed, although with low stability (Cai and Pease 1992;Hedley et al 1990). Thus, transcribed pseudogenes could be using [32m, further limiting the amount of ~32m available.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is specifically designed for the purification of products ~200 bp. Alternatively, purification may also be achieved by electroelution (10) or by a modification of the freeze-squeeze technique. (2~ To purify DNA by the freeze-squeeze method, the band of DNA fragment of interest is excised from an agarose gel, macerated, transferred to a microcentrifuge tube, and frozen at -70~ for 1 hr (or overnight at -20~ The frozen gel is thawed at 37~ for I hr, transferred to an Ultrafree-MC filter unit (Millipore, Bedford, MA) or a Spin-X filter unit (Costar, Cambridge, MA), and centrifuged at 14,000 rpm for 20 min at room temperature.…”
Section: S Purification Of Pcr and $Oeing Productsmentioning
confidence: 99%
“…The sequence data support such a relationship among these class I genes (Rubocki et al 1990;Lee et al 1988). Recently, Cai and Pease (1992) isolated three distinct H-2 v cDNA clones, all of which share the characteristics of D/L locus genes, and suggested that the D and L loci may have their origin in an ancestral family of D/L loci, rather than in a single ancestral locus such as the D. The presence of a Bat-lb gene in this haplotype suggests that the same unequal recombination was involved at some point in the evolution of all three haplotypes, d, q, and v.…”
mentioning
confidence: 99%